2017
DOI: 10.19175/recom.v7i0.1824
|View full text |Cite
|
Sign up to set email alerts
|

Acompanhamento por telefone no p�s-alta dos pacientes onco-hematol�gicos: revis�o integrativa da literatura

Abstract: RESUMOObjetivo: analisar a produção científica acerca do acompanhamento, por telefone, pelo enfermeiro, no pós-alta do paciente com doença onco-hematológica, na redução do evento de readmissão hospitalar. Método: trata-se de uma revisão integrativa da literatura. Tal revisão visa responder à seguinte questão de pesquisa: A intervenção no acompanhamento por telefone, pelo enfermeiro, no pós-alta, reduz a readmissão hospitalar dos pacientes com doença onco-hematológica? A pesquisa foi realizada nas seguintes bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…In this study, one sought to evaluate the symptoms presented after the surgical procedure for patients randomized to the intervention group, in which it was possible to notice that pain was the most prevalent symptom in all telephone contacts, followed by diarrhea, lack of appetite, nausea and vomiting. In a study on telephone follow-up after hospital discharge with onco-hematological patients, it was demonstrated that the most common symptoms presented at home were nausea, mucositis, constipation and fatigue, and that their knowledge and management through the follow-up is the differential to make them less intense and even possible to be controlled by the patients themselves, promoting selfcare and better quality of life (15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, one sought to evaluate the symptoms presented after the surgical procedure for patients randomized to the intervention group, in which it was possible to notice that pain was the most prevalent symptom in all telephone contacts, followed by diarrhea, lack of appetite, nausea and vomiting. In a study on telephone follow-up after hospital discharge with onco-hematological patients, it was demonstrated that the most common symptoms presented at home were nausea, mucositis, constipation and fatigue, and that their knowledge and management through the follow-up is the differential to make them less intense and even possible to be controlled by the patients themselves, promoting selfcare and better quality of life (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nurses' practice associated with monitoring can produce significant changes in the ability to adjust to the new health condition, highlighting the importance of technical and clinical knowledge of the nurses' interventions, with this monitoring being carried out in several sectors. Oncology is a productive field for the use of telehealth technology, since patients require long periods of care, with careful and consistent monitoring (15) . A study showed that postoperative follow-up by telephone, already common in developed countries, can be transposed to Brazil, even within the scope of the Unified Health System -Sistema Único de Saúde (SUS), due to its low cost and high adherence to treatment, but it is still not widely used for surgical patients (13,21) .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, telephone interventions are important nursing tools for achieving and maintaining closer contact with patients. As such, they have been used for post-discharge follow-up strategies in different contexts (de Sousa et al, 2017), including assessments of discharge guidance and behavioral interventions in therapeutic compliance, rehospitalizations and mortality in patients with heart failure (Oscalices et al, 2019), programs designed to reduce absenteeism for return appointments to receive examination results (Nicolau et al, 2017), and assessments of the selfefficacy among puerperal women in regard to the duration and exclusivity of breastfeeding (Chaves et al, 2019). While no national studies have examined the use of telephone interventions for guiding colonoscopy patients in the process of bowel preparation, a Chinese study showed that reeducation of patients in colonoscopy preparation via telephone significantly improved the quality of bowel preparation (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…O paciente com doença onco-hematológica, quando tem alta hospitalar, vai para a sua residência com condições clínicas estáveis, porém não totalmente recuperados. Assim, se não Research, Society andDevelopment, v. 9, n. 9, e413997405, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7405 acompanhado de perto, pode apresentar complicações, com consequente agravamento do quadro clínico, culminando, portanto, com readmissões e, possivelmente, em aumento das morbimortalidades (Sousa, Espírito Santo, Pinheiro, 2017).…”
Section: Introductionunclassified
“…Acompanhá-los no domicílio, através da consulta telefônica, possibilita que tais riscos e complicações sejam precocemente identificados e, prontamente, assistidos, a fim de evitar agravamento do quadro clínico, reduzir as readmissões hospitalares e a mortalidade (Sousa, Espírito Santo, Pinheiro, 2017 (Sousa, Espírito Santo, Santana, Lopes, 2015) e que por semelhança fisiopatogênica estão presentes também nos pacientes com linfoma. Estes DE foram aplicados aos participantes da pesquisa previamente a intervenção de enfermagem a Research, Society and Development, v. 9, n. 9, e413997405, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7405 6 fim de detectar os DE, e consequentemente as demandas de cuidados de enfermagem mais prevalentes.…”
Section: Introductionunclassified